2017
DOI: 10.1016/j.biortech.2017.06.157
|View full text |Cite
|
Sign up to set email alerts
|

Environmental economics of lignin derived transport fuels

Abstract: This paper explores the environmental and economic aspects of fast pyrolytic conversion of lignin, obtained from 2G ethanol plants, to transport fuels for both the marine and automotive markets. Various scenarios are explored, pertaining to aggregation of lignin from several sites, alternative energy carries to replace lignin, transport modalities, and allocation methodology. The results highlight two critical factors that ultimately determine the economic and/or environmental fuel viability. The first factor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Lignin is a phenolic biopolymer that is produced in larger quantity of $50 000 000 tons each year, and due to its aromatic and inhomogeneous complex chemical structure, it is habitually used for combustion of pulps and paper industry boilers. [16][17][18][19] Traditionally, 15-33 wt% of lignin contents are present in any biomass; 20,21 Table 1 shows the percentage of lignin in basic wood types. Usually, lignin is based on three aromatic alcohols, sinapyl, coniferyl, and p-coumaryl, as shown in Fig.…”
Section: Lignin Its Functionality and Redox Activitymentioning
confidence: 99%
“…Lignin is a phenolic biopolymer that is produced in larger quantity of $50 000 000 tons each year, and due to its aromatic and inhomogeneous complex chemical structure, it is habitually used for combustion of pulps and paper industry boilers. [16][17][18][19] Traditionally, 15-33 wt% of lignin contents are present in any biomass; 20,21 Table 1 shows the percentage of lignin in basic wood types. Usually, lignin is based on three aromatic alcohols, sinapyl, coniferyl, and p-coumaryl, as shown in Fig.…”
Section: Lignin Its Functionality and Redox Activitymentioning
confidence: 99%
“…The marine sector is conceivably more favorable in this regard than the road and aviation sectors, as marine engines are more tolerant of lower-quality fuel. For example, it has been proposed that unprocessed lignin pyrolysis oil can substitute low-sulfur marine gas oil ( Obydenkova et al., 2017 ). However, it has also been shown that crude bio-oil cannot be blended with current marine fuels in any proportion such that the resultant mixture meets marine fuel specifications ( Chong and Bridgwater, 2017 ).…”
Section: Bio-oilmentioning
confidence: 99%
“…A very comprehensive paper covering this analysis for second‐generation feedstock is reported by Obydenkova et al . ) Currently, Beta Renewables (the Crescentino Bioethanol Plant) is not a real biorefinery under current definitions. Nevertheless, this case is considered because this plant can upgrade to a biorefinery, for example by using the residues of the process as a raw material for the generation of other added‐value products.…”
Section: Classification Of Biorefineriesmentioning
confidence: 99%